Newcastle disease, infectious bursal disease and EDS ’76 antibodies in indigenous Nigerian Local Chickens (1999)
A serological survey was conducted to determine the prevalence of Newcastle disease (ND), infectious bursal disease (IBD) and egg drop syndrome ’76 (EDS ’76) antibodies in indigenous Nigerian local chickens. The survey was carried out in Ekiti, Osun, Oyo, Ogun and Lagos States in southwestern Nigeria. Out of 2010 serum samples assayed for ND, 1890 (94%) were positive. 720 (34%) out of 2090 samples were positive for IBD, while 500 (29%) out of 1740 samples were positive for EDS ’76. The prevalent rates are high enough to suggest that ND, IBD and EDS ’76 are still very active in these indigenous chickens. The implications of these findings in the control of ND, IBD and EDS ’76 in the commercial exotic poultry flocks are discussed.